The Barcelona Brain Health Initiative: A Cohort Study to Define and Promote Determinants of Brain Health - Cattaneo, Gabriele; Bartrés-Faz, David; Morris, Timothy P.; Sánchez, Javier Solana; Macià, Dídac; Tarrero, Clara; Tormos, Josep M.; Pascual-Leone, Alvaro (Frontiers in Aging Neuroscience, 2018)
The Barcelona Brain Health Initiative (BBHI) is an ongoing prospective longitudinal study focused on identifying determinants of brain health. The main objectives are: (i) to characterize lifestyle, cognitive, behavioral and environmental markers related to a given individual’s cognitive and mental functions in middle to old age, (ii) to assess the biological determinants predictive of maintenance of brain health, and (iii) to evaluate the impact of a controlled multi-dimensional lifestyle intervention on improving and maintaining brain health. The BBHI cohort consists of >4500 healthy participants aged 40 to 65 years followed through online questionnaires (Phase I) assessing participants’ self-perceived health and lifestyle factors in seven different domains: overall health, physical exercise, cognitive activity, sleep, nutrition, social interactions, and life purpose. In Phase II a sub-group of 1,000 individuals is undergoing detailed in-person evaluations repeated at two-yearly intervals. These evaluations will provide deep phenotyping of brain function, including medical, neurological and psychiatric examinations, assessment of physical fitness, neuropsychological assessments, structural and functional brain magnetic resonance imaging, electroencephalography and perturbation-based non-invasive brain stimulation evaluations of brain activity, as well as collection of biological samples. Finally, in Phase III a further sub-group of 500 participants will undergo a similar in-person assessment before and after a multi-dimensional intervention to optimize lifestyle habits and evaluate its effects on cognitive and brain structure and function. The intervention group will receive remote supervision through an ICT-based solution, with the support of an expert in health and lifestyle coaching strategies aimed at promoting adherence. On the other hand, the control group will not have this coaching support, and will only receive education and recommendations about healthy habits. Results of this three-part initiative shall critically contribute to a better understanding of the determinants to promote and maintain brain health over the lifespan.